Vitamin D and women’s reproductive health (literature review) - Ya. Z. Zaydieva; V. E. Balan (Медицинский совет, 2018)
Vitamin D and women’s reproductive health (literature review). Literature search the relationship between vitamin D and fertility in women рerformed in Pubmed. The vitamin D receptor (VDR) and vitamin D metabolizing enzymes are found in reproductive tissues of women. Moreover, we present evidence that vitamin D is involved in female reproduction including IVF outcome and polycystic ovary syndrome (PCOS). In PCOS women, low 25-hydroxyvitamin D (25(OH)D) levels are associated with obesity, metabolic, and endocrine disturbances and vitamin D supplementation might improve menstrual frequency and metabolic disturbances in those women. Moreover, vitamin D might influence steroidogenesis of sex hormones (estradiol and progesterone) in healthy women and high 25(OH)D levels might be associated with endometriosis.